Incorporation of the Competencies of Humanization, Ethics, Leadership, and Nursing Management into Nursing Curricula in Spain. - Cortés Borra, Albert; Jaén Ferrer, Pedro; Gea-Caballero, Vicente; Martínez Riera, José Ramón (Investigación & Educación en Enfermería)
Objective. The aim of the study was to analyze the integration of these competencies into the curricula of the Bachelor’s Degree in Nursing in Spain. Methods. A descriptive and comparative study was conducted through documentary and content analysis of the current curricula of the Bachelor’s Degree in Nursing from 51 Spanish universities (39 public and 12 private). Data were obtained from the Official State Gazette and institutional repositories. The presence, explicitness, and credit load (ECTS) of the competencies studied were analyzed using a qualitative-quantitative approach. Results. Ethics and the humanization of care showed a high level of integration and low variability among universities. Management demonstrated an intermediate level of development, while nursing leadership was the least explicitly addressed competency, generally embedded within managementrelated courses. Considerable curricular heterogeneity and qualitative differences were observed between public and private universities, with greater explicit emphasis on leadership and humanization in some private institutions. Conclusion. Although curricula show acceptable levels of integration of ethics and humanization competencies, structural weaknesses exist in developing nursing leadership. Greater curricular harmonization is required to explicitly strengthen clinical leadership, strategic management, and deliberative ethics to ensure education oriented toward humanized leadership.